Differences between postmortem computed tomography and conventional autopsy in a stabbing murder case (Clinics, 2014)
Objective: The aim of the present work is to analyze the differences and similarities between the elements of a conventional autopsy and images obtained from postmortem computed tomography in a case of a homicide stab wound. Method: Comparison between the findings of different methods: autopsy and postmortem computed tomography. Results: In some aspects, autopsy is still superior to imaging, especially in relation to external examination and the description of lesion vitality. However, the findings of gas embolism, pneumothorax and pulmonary emphysema and the relationship between the internal path of the instrument of aggression and the entry wound are better demonstrated by postmortem computed tomography. Conclusions: Although multislice computed tomography has greater accuracy than autopsy, we believe that the conventional autopsy method is fundamental for providing evidence in criminal investigations.